SALVATION IN SAIVA SIDDHANTA - Manninezhath, Thomas (Journal of Dharma, 1997)
Salvation of the human self is a very, favourite theme in all religions of the world. Although each religion approaches this doctrine from its own weltanschauung, salvation, essentially for all religious traditions, is a deliverance from bondage, evil, sin and suffering. It is a passage from the negative, bound state of being to a positive, blissful state of life. This article is an attempt to understand the concept of salvation in one of the Indian theistic traditions, namely, the Saiva Siddhanta school of the Tamil Tradition. The study is based on the philosophical and mystical hymns of Tayumanavar (Tayumanaswamikal Patal (TP) of 17th century A.D.and the classical Saiva Siddhanta philosopical work Sivananapotam (Skt.Sivajnanabodham) of Meykantar (13th century A.D.).